Reformulation of the Role of Regional Development Banks as Agents of Regional Catalyst: The Case of Indonesia - Umanto, Umanto; Ikasari, Novita (UI Scholars Hub, 2019)
Regional development banks (RDB) in Indonesia are constitutionally mandated to be the economic and social catalyst for local development, a role which requires banks to finance ‘unprofitable’ projects. The incompatible functions are resulted in reservations within RDB to maximize their resource allocation potential. This paper is aimed at evaluating RDB’s catalyst role and at proposing a refinement to the current role which would enable RDBs to achieve their expected goals. This research uses descriptive statistics of RDBs’ loan performance from 2012 to 2017 to establish RDBs’ performance in economic and social areas. Accounts included in this research are third-party funds, productive loans, loan deposit ratio and small business loans. It is evident from the secondary data that RDBs have issues in contributing to local economy generator. Next, data from interviews with senior management team of four RDB’s are analysed to identify critical pillars for formulation of RDBs’ role. Referring to Thorne’s and Du Toit’s framework for development banks (2009) the reformulation of RDBs’ catalyst role starts from stipulating their role in an exclusive and well-defined operating environment. This will allow RDBs to synergize their operations with local development programs. From governance and financial performance perspectives, RDBs can prepare efforts to make an initial public offering as part of a strategy for increasing capital, structuring corporate governance, and enhance corporate value.